You are on page 1of 6

International Journal of Mechanical and Production

Engineering Research and Development (IJMPERD)


ISSN (P): 2249-6890; ISSN (E): 2249-8001
Vol. 9, Issue 2, Apr 2019, 659-664
© TJPRC Pvt. Ltd.

QUALITATIVE ANALYSIS ON SECOND ORDER NEUTRAL

DELAY DIFFERENCE EQUATIONS

G. GOMATHI JAWAHAR
Department of Mathematics, Karunya Institute of Technology and Sciences, Coimbatore, Tamil Nadu, India
ABSTRACT

In this paper, the oscillatory and non oscillatory behavior of all solutions of the second order neutral delay
difference equations of the form mentioned by the equation is dealt with.

∆(a n ∆( x n + p n xn−l )) − q n f ( x n−m ) = 0, . Where nεN(n0), {an},{bn },{cn} are positive sequences and l,

m>0.

Examples are provided to illustrate the main results.

KEYWORDS: Oscillation, Non-Oscillation, Neutral, Delay & Difference Equations

Original Article
AMS SUBJECT CLASSIFICATION: 39A10.

Received: Feb 07, 2019; Accepted: Feb 27, 2019; Published: Mar 23, 2019; Paper Id.: IJMPERDAPR201966

1. INTRODUCTION

Consider the second order neutral delay difference equation of the form

∆(a n ∆( x n + p n xn−l )) − q n f ( x n−m ) = 0, (1.1)

Where, nεN(n0), {an},{bn },{cn} are positive sequences and l, m>o. ∆ is the forward difference operator
defined by ∆ yn = yn+1 – yn. f is a continuous function such that uf (u) ≠ o for ∀ u ≠ o.

By a Solution of (1.1), we mean a real sequence {xn} which satisfies (1.1) for all n ε N(no). A solution
{xn} of (1.1) said to be oscillatory if the terms {xn} of the sequence are not eventually positive or not eventually
negative. Otherwise, it is called non oscillatory.

In the past few years, there has been an increasing interest in the study of oscillatory and non oscillatory
behavior of all solutions of (1.1). Followings this trend, in this paper, we obtain some sufficient conditions for the
oscillation and non oscillation of all solutions of (1.1). Examples are provided to illustrate the main results.

2. MAIN RESULTS
Theorem 2.1

Let ρn be defined such that ∆ ρn > o and ∆ (an-m ∆ ρn) < o for ∀nεN(n0). Also, assume that

A1 : fnm> fn fm,

www.tjprc.org SCOPUS Indexed Journal editor@tjprc.org


660 G. Gomathi Jawahar


u
A2: ∑ < ∞ , for some ε > 0.
u = ε f (u )

n
If lim sup ∑ ρ s + 1 q s f (1 − p s − m ) = ∞
, then every solution of equation (1.1) is oscillatory.
n→∞
s=N 0

Proof: Suppose xn be a non oscillatory solution of (1.1). Without loss of generality we may assume that

xn is eventually positive.

Define zn = xn+ pn xn-l, (2.1)

Now equation (1.1) becomes,

∆ (an∆zn) -qn (zn-m- pn-m xn-m-l) =o

From A1, ∆ (an∆zn) -qn (1-pn-m) f (zn-m) < 0 (2.2)

Define wn = ρ n { an ∆zn }/ f(zn-m) then wn >0.

Now, wn f (zn-m)/ ρn = an ∆zn

Equation (2.2) becomes,

∆ (an∆zn) < qn f(1-pn-m) f (zn-m)

∆ (wn f(zn-m) )/ ρn < qn f (1-pn-m) f (zn-m)

{ρn ∆ ( wn f (zn-m) – wn f (zn-m) ∆ ρn } /ρnρn+1 < qn f (1-pn-m) f (zn-m)

{ ρn wn f (zn+1-m) – ρn wn f (zn-m) + ρn f (zn-m) wn+1- wnf (zn-m)ρn+1}/ρnρn+1 < qn f (1-pn-m) f (zn-m)

ρn f (zn-m) ∆ wn < qn f (1-pn-m) f (zn-m)ρn ρn+1-wn ( ρn f(z n+1-m) – ρn+1 f (zn-m))

∆wn < ρn+1 qn f (1- pn-m) – ρn an ∆ zn { [ρn f(zn+1-m)-ρn+1 f(zn-m)]/ρn f(zn-m)}

f(zn-m)

∆wn< ρn+1 qn f (1- pn-m) – an ∆ zn {[ρn f(zn+1-m) – ρn+1 f (zn-m)]/ (f (zn-m )2}

Since {an ∆zn} is a decreasing sequence, we have

Sequence, an ∆zn < an-m ∆ zn-m, for n ≥ No.

∆wn < ρn+1 qn f (1-pn-m) –{an ∆znρn f (zn+1-m)/ (f ( zn-m) 2}+ ρn+1 an ∆zn/f (zn-m)

∆wn < ρn+1 qn f ( 1-pn-m) +[ ρn+1 a n-m ∆ zn-m/f(zn-m)]

ρn+1 qn f (1- pn-m) < ∆wn + ρn +1 an-m ∆ zn-m

f ( zn-m)

∑ρ
s = N0
s +1 qs f ( 1- ps-m) < ∞, for n ≥ N0, which contradicts the given condition. Hence every solution of (1.1) is

Impact Factor (JCC): 7.6197 SCOPUS Indexed Journal NAAS Rating: 3.11
Qualitative Analysis on Second Order Neutral Delay Difference Equations 661

oscillatory.

Theorem 2.2

Let xn be a non oscillatory solution of (1.1) and assume

A3: [F(u)/u] > γ >0, and 0≤pn≤1.


A4: ∑ γq (1- p
s =n
s s-m) < ∞. Suppose, the sequence { vn} is defined as, vn1 = Qn,


vnk + 2 = Qn,+
v
∑{Q v
s =n
s sk +1 / a s −m }

n−m ∞
Then, lim sup( ( ∑1 / a s )(−Qn + ∑ (Qs2 / a s −m ))≤1.
n→∞
s=N0 s=n

Proof

Let xn be a non oscillatory solution of (1.1). Without loss of generality assume xn>0, for n≥N0.

Let zn = xn + pn xn-l

Equation (1.1) becomes,

∆ (an ∆zn ) - qn f (zn-m – pn-m xn-l-m) =o

∆ (an ∆zn ) = qn f (zn-m – pn-m xn-l-m)

From A3, ∆ (an ∆zn ) - γ qn f (zn-m – pn-m xn-l-m) < o

Since zn> xn,

∆ (an ∆zn ) - γ qn (1- pn-m )pn-m ) zn-m < 0

Define vn = an ∆zn/zn-m, vn > 0

∆vn = zn-m ∆ (an ∆zn) – an ∆zn ∆(zn-m) / zn+1-m zn-m

{∆vn zn-mzn+1-m +an ∆zn ∆(zn-m) } / zn = ∆ (an ∆zn)

Equation (2.3) becomes,

{∆vn. zn-m zn+1-m +an ∆zn ∆zn-m }/zn-m < γ qn (1- pn-m)

∆vn zn+1-m +[an ∆zn ∆zn-m/zn-m]< γ qn (1- pn-m ) zn-m

∆vn < γ qn (1- pn-m ) – {vn2 /an-m} (2.4)

This implies {vn} is an decreasing sequence and lim vn exists.


n→∞

Taking summation of (2.4) from n to N,

www.tjprc.org SCOPUS Indexed Journal editor@tjprc.org


662 G. Gomathi Jawahar

N ∞ 2

vN - vn ≤ ∑ γ q (1 − p s s −m )−∑
vs
a s −m
(2.5)
S =n s =n

∞ 2
v
Since lim VN exists, ∑
n→∞
s
< ∞
δ = n a s − m

This implies lim vN = o


n→∞


Equation(2.5) becomes, - vn < Qn- ∑v
s =n
2
s / a s −m


vn≥ -Qn+ ∑v
s =n
2
s / a s −m , n≥N0.

Since vn ≥ Qn,

∞ ∞ 2

∑ Qs vs / as−m < ∑ vs / as−m


s= N0 s = N0
(2.6)

Equation (2.6) becomes,


vn ≥- Qn + ∑Q v
s =n
s s / a s −m , for n≥N0.

Also, an ∆zn is decreasing sequence for n≥N0.

n−m
1
z n−m 1 Σ ( )as∆zs n−m
1 n−m
1
Σ
as
Thus = = z N0 + s = No
≥ {a s ∆ z s ∑ } / an =
an∆zn vn an∆zn s= N 0 as s = No as

n−m
1
Hence vn Σ
s = No as
≤1

n−m
1
Since an >0, lim sup vn
n→∞ Σ
s = No as
≤ 1. (2.7)


vn2 =-Qn + ∑Q v
s =n
s s1 / a s −m ,

since vn2 ≤vn, equation (2.7) becomes,

n−m
1
lim sup vn2
n→∞ Σ
s = No as
≤1 (2.8)

Since vs1 = Qs, equation (2.8) becomes,

Impact Factor (JCC): 7.6197 SCOPUS Indexed Journal NAAS Rating: 3.11
Qualitative Analysis on Second Order Neutral Delay Difference Equations 663

∞ n−m
1
lim sup ( -Qn+
n→∞
∑ Qs2 / as−m )
s =n
Σ
s = No as
≤ 1. This completes the proof.

Theorem 2.3

Let xn be a non oscillatory solution of (1.1) and zn = xn+ pn xn-l. If {an} is an increasing sequence, then {zn ∆zn} is
eventually negative.

Proof

Without loss of generality, we may assume that xn-m-l > 0 for n≥ No.

Then zn> o.

Equation (1.1) becomes ∆ (an ∆zn) = qn f ( xn-m) < 0 for n≥ No. (2.9)

Hence, an ∆zn is decreasing sequence.

To prove ∆ zn < 0

Suppose to the contrary that there exists n1> N0

Such that ∆ z n1 > 0.

From (2.9), ∆ (an ∆ zn) < 0.

This implies ∆ (an ( zn+1 – zn) < 0.

⇒ ∆ (an zn+1 – an zn) <0.

an+1 zn+2 – an zn+1 – (an+1 zn+1 – an zn) <0.

an zn < an zn+1 + an+1 zn+1 – an+1 zn+2.

zn <an zn+1 – an+1 ∆zn+1. (3.0)

Hence zn< 0.

This contradicts the fact that zn >0. Hence ∆zn <0. This completes our proof.

3. EXAMPLES
Example 3.1

Consider the difference equation

∆ (n ∆ ( xn+nxn-1) - ( 2n-1) x n-13 = 0, for n>0 (3.1)

Here an= n, pn = n, qn= 2n-1, l= 1, m=1

All conditions of theorem (2.1) are satisfied. Hence all solutions of (3.1) are oscillatory. one such solution is (-1)n.

Example 3.2

Consider the difference equation,

www.tjprc.org SCOPUS Indexed Journal editor@tjprc.org


664 G. Gomathi Jawahar

1 1 xn−1
∆( ∆ (xn+ xn-1) ) - = 0, for n>1 (3.2)
n n −1 n(n + 1)(n − 1)

Here, an =1/n, pn= 1/n-1, qn = 1 /n(n+1)(n-1), l=1, m=1.

All conditions of theorem (2.2) are satisfied and n is a non-oscillatory solution of (3.2).

∞ n−m
1
Hence, lim sup ( -Qn+
n→∞
∑ Qs2 / as−m )
s =n
Σ
s = No as
≤ 1.

4. CONCLUSIONS

In this paper, by using summation averaging techniques and comparison principle some new oscillation criteria
for second order neutral delay difference equation is obtained. Examples are provided to illustrate the results. Further none
of the results in the papers [3-8] can be applied to Eq. (1.1) to yield any conclusion.

REFERENCES

1. R. P Agarwal, ‘Difference Equations and Inequalities’-Marcel Dekker, Newyork (1992).

2. I. Gyori and G. Ladas, ‘Oscillation theory of Delay differential equations with applications’-Clarendon press, oxford(1991).

3. M. K. Grammatikopoulos, G. Ladas and A. Merimardou, Oscillations of second order neutral differential equations, Radovi
Mat.1, 267-274, (1985).

4. S. R Grace and S. R. Lalli, Oscillations of nonlinear second order neutral delay differential equations, Mat.3,77-84,(1987).

5. El-Sheikh, M. M. A., Sallam, R. A., & Nahed, M. M. New criteria for oscillation of second order nonlinear dynamic equations
with damping on time scales. IJRANSS, 3, 79-86.

6. S. R Grace, M. P Chen and B. S Lalli, Oscillation criteria for second order neutral differential equations, sea Bull.
Math.14,91-101, (1990).

7. G. Ladas and Y. G sficas, Oscillations of higher order neutral delay differential equations, Austral. Math. Soc.(seriesB) 27,
502-511,(1986)

8. G. Ladas and Y. G sficas, Oscillations of neutral delay differential equations, canad. Math. Bull. 29, 438-445,(1986).

9. Shaalini, J. V., & Pushpam, A. E. K. Application of RKHEM Method for Solving Delay Differential Equations with Constant
Lags.

10. Ozkan Ocalan, ‘Oscillation of neutral differential equation with positive and negative coefficients’- J. Math, Anal. Appl.
331(2007), pp.644-654.

Impact Factor (JCC): 7.6197 SCOPUS Indexed Journal NAAS Rating: 3.11